Pengaruh Penambahan Bawang Putih dan Lama Fermentasi Terhadap Mutu Mikrobiologis dan Organoleptik Bebontot - Nyoman Semadi Antara; I Wayan Sweta Partama; Luh Putu Wrasiati (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2017)
Bebontot is one of fermented meat product produced in Bali island, Indonesia. Chopped porkand fat are mixed with spices and salt. The mixer are wrapped in spatha of areca tree (Arecacatechu L.) and fermented for several days to produce bebontot. The research was conductedto find out the effects of garlic in bebontot formulation and fermentation time on thebebontot quality. The result showed that the addition of garlic could suppressed significantlythe growth of Enterobacteriaceae and Staphylococcus aureus, but not for lactic acid bacteria(LAB) and micrococci bacteria. During fermentation all investigated bacteria were changewhere LAB increased and Enterobacteriacea and Staph. aureus decreased during process offermentation. The organoleptic characteristicts of bebontot were influenced significantly bycombination of both treatments.